DEN DANSKE FRUGT- OG GRØNTSEKTOR: UDVIKLING, UDFORDRINGER OG MULIGE INITIATIVER - Hansen, H. (Tidsskrift for Landøkonomi, 2008)
DEN DANSKE FRUGT- OG GRØNTSEKTOR: UDVIKLING, UDFORDRINGER OG MULIGE INITIATIVER